PENGARUH ROLE AMBIGUITY DAN KONFLIK PERAN TERHADAP INTENSITAS KELUAR DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Bank Umum Wilayah Salatiga) - Muhdiyanto, 11.5202.0083 (Students Journal of Accounting and Banking, 2013)
The goal of this research is to test the effect of role ambiguity and role conflict on the influence with job stress as in financial institute bank at Salatiga religion. There are several hypotheses to be tested in this research. (1) There is effect role ambiguity on job stress (2) There is role conflict on job stress. (3) There is effect role ambiguity on intent to leave (4) There is role conflict on intent to leave. (4) There is job stress on intent to leave. A survey was conducted by using questionnaires from previous research. The questionnaires were sent to 12 financial institute bank at Salatiga religion. The sample consisted of 170 respondents. Validity tests and reliability tests were used to test the questionnaires content. The study employs a moderated regression analysis (MRA) to analyze the hypotheses and ass it by SPSS 16.00 from windows programs. The result supported of hypotheses 1 and 2, but not supported hypothesis 3, 4, and 5 of study. A thorough discussion on the relationship among the variables is presented in this paper. Key word: role ambiguity, role conflict, job stress and intent to leave